Enhancement of apixaban's solubility and dissolution rate by inclusion complex (β-cyclodextrin and hydroxypropyl β-cyclo¬dextrin) and computational calculation of their inclusion complexes - Zainab N. Salman; Israa Al-Ani; Khaldun M. Al Azzam; Bashar JM. Majeed; Hassan H. Abdallah; El-Sayed Negim (International Association of Physical Chemists (IAPC), 2023)
Background and Purpose: Apixaban (AP) is a factor X inhibitor, an orally active drug that inhibits blood coagulation for better prevention of venous thromboembolism. It has poor solubility, dissolution rate and low bioavailability. The aim of this study was to improve the aqueous solubility and dissolution rate of oral AP as a step to enhance its bioavailability by preparing it as an inclusion complex with beta- and hydroxy propyl beta-cyclodextrin. Experimental Approach: A simple, rapid method of analysis of AP was developed using ultraviolet spectrophotometry (UV) and partially validated in terms of linearity, precision and accuracy, recovery, and robustness. AP was prepared as a complex with beta cyclodextrin (βCD) and hydroxy propyl beta cyclodextrin (HPβCD) in weight ratios 1:1, 1:2, and 1:3 by kneading, solvent evaporation and spray drying methods and characterized by Fourier transfer infra-red (FTIR), differential scanning calorimetry (DSC), and percent drug content in each of the prepared complex. Using the computer simulation, the interactions of AP with βCD and HPβCD were investigated. Key Results: The phase solubility study showed that the solubility of AP was greatly enhanced from 54×10-3 mmol /L to 66 mmol/L using HPβCD with acceptable stability constant. Computer docking supports the formation of a stable 1:1 complex between AP and CD's. The dissolution test results showed that the complex gave a significantly higher percentage of drug release (95%) over one hour compared to the free AP (60%) (p<0.05). Conclusion: AP- HPβCD complex in the ratio of 1:2 (w/w) can significantly improve the solubility and in vitro dissolution rate of AP.